EVALUASI TINGKAT KEBERHASILAN TUMPATAN KLAS III DAN KLAS IV DENGAN BAHAN RESIN KOMPOSIT DAN SEMEN IONOMER KACA (Penelitian pada Anak Usia 0-14 Tahun di RSGM UMY) - Restia Rahmadhani (FKG 15 UMY 536, 2015)
*536 Dental caries can be happened in anterior and posterior teeth. Caries in anterior teeth is an evidence of excessive caries. Dental caries more attack in children at school age. About 80-95% children under 18 years old was attacked by dental caries. Dental caries in children need an effective dental treatment. The aim of this study is to measure the success rate of class III and clas IV restoration of resin composie and glass ionomer cement on children aged 0-14 years at RSGM UMY. Research methods of this study is observasional descriptive and the data are collected by using retospective study in August 2015 at RSGM UMY. The data was analyzed with descriptive statistical analysis and showed precentage of success using resin composite clas III restoration is 94,7%. The precentage of success using glass ionomer cement clas III restoration is 88%. The precentage of success using resin composite clas IV restoration is 93,7%. The precentage of success using glass ionomer cement clas IV restoration is 90,5%. The result of this research, both is a had successful rate clas III and clas IV restoration with resin composite and glass ionomer cement in children who are 0-14 years old at RSGM UMY. Keywords : restoration class III, restoration clas IV, resin composite, glass ionomer cement, and children aged 0-14 years.